RANCANG BANGUN DAN PENGUJIAN ALAT PRODUKSI BIOGAS DARI KOTORAN SAPI DENGAN VARIASI JUMLAH MIKROBA - Kalsum, Leila (KINETIKA, 2018)
Biogas is an alternative energy in the form of gas produced from organic materials. The biggest component of biogas is methane (CH4 , 54-80% volume) and carbon dioxide (20-45% volume) and a small amount of oxygen, H2 , N2 and H2S. The process of making biogas is carried out in fermentation, namely the process of forming methane gas under anaerobic conditions with the help of anaerobic bacteria in a digester so that methane (CH4 ) and carbon dioxide (CO2 ) gases are produced which are larger than hydrogen (H2 ), nitrogen (N2 ) and sulfide acid (H2S). This study aims to make biogas from organic waste materials and cow dung by conducting variations of microorganisms to see how much biogas is produced with a short span of time. The variation of Green Phoskko-7 (GP-7) microorganisms is 250 gr, 350 gr and 450 gr with a fixed composition and material concentration of 133 kg of cow dung: 66 liters of water (2: 1) which is fermented for 7 days with a fixed temperature 35ÂºC. The results of this study showed that the optimum amount was 450 grams of GP-7 with a volume of 0.338467 m3 and a methane level of 33.492 mol%